Signs the secret language of the universe - Jackson, Laura Lynne (New York Dial Press, 2019)
"Laura Lynne Jackson is a psychic medium and the author of the New York Times bestseller The Light Between Us. She possesses an incredible gift--the ability to communicate with loved ones who have passed, convey messages of love and healing, and impart a greater understanding of our interconnectedness. Though her abilities are exceptional, they are not unique, and that is the message at the core of this book. Understanding "the secret language of the universe" is a gift available to all. As we learn to ask for and recognize signs from the other side, we will start to find meaning where before there was only confusion, we will see light in the darkness. We may decide to change paths, push toward love, pursue joy, and engage with life in a whole new way. In Signs, Jackson is able to bring the mystical into the everyday. She relates stories of people who have experienced these uncanny revelations and instances of unexplained synchronicity, as well as those drawn from her own experience. There's the producer whose lost child appears to her as a deer that approaches her unhesitatingly at a highway rest stop; the name tag of an ER nurse that lets a terrified wife know that her husband will be okay; the Elvis Presley song that arrives at the exact time of her own father's passing; and many others. This is a book that is both inspiring and practical, deeply comforting and wonderfully motivational in asking us to see beyond ourselves to a more magnificent universal design"--
Oranges -- Cereal in the car -- Teams of light -- I carry your heart -- Dragonflies and deer -- Buddies on the other side -- Hearts and playing cards -- Hummingbirds and light -- Giraffes, Eiffel Towers, and a song about cats -- Default signs, dreams, and intuition: tuning in to the secret language -- Bringing it home -- 1379 -- Ghost calls -- Birds of a feather -- Street signs -- Dancing candles -- Turtles and mermaids -- The connector -- All creatures great and small -- Groundhogs -- How to co-create your own language -- Camouflage, a gun, and a new assignment -- Babies and bears -- Flickering lights and sparks -- Bows and clovers -- Rainbows -- Tiny whispers -- A gift of love and forgiveness -- Surrender -- How to shine brightly -- Shine on.
108259
Keywords: Spiritualism; Omens; Prophecies; Prophecies